Investigation of Impact of Aggregate Coating by Bitumen on Change of Micro Texture Values (European Journal of Engineering Science and Technology, 2020)
Asphalt pavement micro texture values primarily depend on aggregate properties used in asphalt pavement mixture and by aggregate surfaces is secured the basic contact medium with vehicle tires. It often happens that new asphalt surfaces have not required skid resistance properties and is needed a certain period of time to eliminate film of bitumen binder which is coating the aggregate grain on the surface of pavement by action of vehicles. In most cases, the investigation of the aggregate micro texture impact on the pavement skid resistance properties is carried out under laboratory conditions and generally relates only to measurements on natural aggregate samples (without bitumen). However, due to coating of aggregate by bitumen binder, valleys between the individual peaks of aggregate are filled. Obviously, it can be supposed that the usage of high amount of bitumen content can leads to decreasing of aggregate micro texture values. From this point of view, it can be expected that change in micro texture values depends on the content of binder in the asphalt mixture. Particular aggregate grains were taken from asphalt mixtures samples (AC 8, AC 11 and SMA 11) produced in the laboratory, in order to determine the impact of aggregate coating by bitumen binder on micro texture change. Each usage asphalt mixture was produced with three different bitumen binder contents. Digital image analysis method was used for subsequent evaluation. Changes in the micro texture values depending on the amount of used bitumen binder and also on the calculated theoretical bitumen film thickness are investigated in the conclusion.